Anellovirus protein encoded by ORF2/3 functions as the viral replication initiation protein - Nicole Boisvert; Stephanie Thurmond; Carmen Elenberger; Patricio Jeraldo; Cato Prince; Nolan Sutherland; José Melo; Ken Tsheowang; Cameron Dodier; Maciej Nogalski; Dinesh Verma; Geoffrey Parsons; et al. (Proceedings of the National Academy of Sciences, 2025)
Anelloviridae is a family of single-stranded DNA viruses that are thought to be nonpathogenic and commensal. Despite their ubiquitous presence in human populations, little is known about the anellovirus mechanism of replication in host cells. We identified the protein coded by ORF2/3 as necessary and sufficient to initiate replication from the minimal origin of replication for viruses of both the Beta- and Alphatorquevirus genera. Supporting this observation, we identified components of the polymerase alpha and BTR (Bloom’s syndrome helicase (BLM), topoisomerase IIIα, RMI1, and RMI2) complexes as interacting with the viral replication initiation protein (Rip) during DNA replication, suggesting a recombination-dependent mechanism of replication that uses host cell machinery to mediate dissolution of replication intermediates. Furthermore, we mapped a 92-bp minimal origin of replication sequence for the Betatorquevirus genus composed of an adenine and thymine (AT)-rich stretch and a portion of the guanine and cytosine (GC)-rich region. Altogether, this study provides insight into the mechanism by which anelloviruses manipulate host cell machinery to facilitate viral genome replication and represents a significant step forward in understanding the complex processes underlying anellovirus replication and persistent infection of these important commensal viruses.